ANALYSIS OF TRANSCRIPTION OF UZBEKI BASED ON ARABIC AND LATIN GRAPHICS (World Economics and Finance Bulletin, 2022)
This article is devoted to the transcription of extra units used in classic works from Arabic graphics to Uzbek language based on Latin graphics and the analysis of mistakes and shortcomings made in this process.
Keywords: Arabic language graphics; Uzbek language based on Latin graphics; transcription; extra unit